ANALISIS KINERJA PEGAWAI PADA PT BANK SUMUT KANTOR PUSAT MEDAN YANG DIPENGARUHI OLEH PELATIHAN KERJA DAN DISIPLIN KERJA - Aisyah, Siti; Ikhwana, Hablil; Efendi Damanik, Rusli (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2025)
After the Covid-19 pandemic, people's behavior demands fast access to banking services. The services provided must be cheap, easy, and also efficient, which are the basic needs of people in the digital era. This is experienced by one of the banking institutions in North Sumatra. This study purpose of analyze the influence of job training, work discipline, and employee performance at PT Bank Sumut Medan, Head Office. The type of research is causal with a quantitative approach. The population of this study was employees of PT Bank Sumut Medan, Head Office, namely 43 people, with a saturated sample determination with the determination of saturated samples as the sampling technique. Data analysis used multiple linear regression techniques. Based on the results of the analysis, both job training and work discipline have a positive influence on employee performance at PT Bank Sumut Medan, Head Office, but the influence is not statistically significant. Work discipline has a greater influence than job training on employee performance at PT Bank Sumut, Medan Head Office. Although both independent variables show a positive relationship with employee performance, job training and work discipline do not have a strong enough influence simultaneously to be considered statistically significant. The results of the determination coefficient test have very low predictive power; only 3.4 percent of the variation in employee performance can be explained by work training and work discipline. Most of the variation in employee performance (96.6%) is explained by other factors that were not studied.